2013
DOI: 10.5194/angeo-31-1035-2013
|View full text |Cite
|
Sign up to set email alerts
|

Relation of zonal plasma drift and wind in the equatorial F region as derived from CHAMP observations

Abstract: In this paper we estimate zonal plasma drift in the equatorial ionospheric F region without counting on ion drift meters. From June 2001 to June 2004 zonal plasma drift velocity is estimated from electron, neutral, and magnetic field observations of Challenging Mini-satellite Payload (CHAMP) in the 09:00–20:00 LT sector. The estimated velocities are validated against ion drift measurements by the Republic of China Satellite-1/Ionospheric Plasma and Electrodynamics Instrument (ROCSAT-1/IPEI) during the same per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The corresponding superrotations are 15, 9, and 3 m/s. Park and Lühr (2013) compared the zonal wind and plasma drift observations of the CHAMP satellite and found that they exhibited the same diurnal variation. Both the plasma drift direction and the zonal wind reversed at 16 LT, and the velocities of the zonal wind during the daytime and nighttime were slightly larger than those of the plasma that is consistent with our simulation results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding superrotations are 15, 9, and 3 m/s. Park and Lühr (2013) compared the zonal wind and plasma drift observations of the CHAMP satellite and found that they exhibited the same diurnal variation. Both the plasma drift direction and the zonal wind reversed at 16 LT, and the velocities of the zonal wind during the daytime and nighttime were slightly larger than those of the plasma that is consistent with our simulation results.…”
Section: Resultsmentioning
confidence: 99%
“…The F‐region zonal wind dynamo can drive the vertical current in the radial direction at the equator, jz=σp(EzUyBx) ${j}_{z}={\sigma }_{p}({E}_{z}-{U}_{y}{B}_{x})$, where σp ${\sigma }_{p}$ is the Pedersen conductivity in the F layer, Ez ${E}_{z}$ is the radial electric field, Uy0.25em ${U}_{y}\hspace*{.5em}$ is the zonal wind, and Bx ${B}_{x}$ is the geomagnetic field in the northward direction (Park & Lühr, 2013). The first term on the right‐hand side represents the contribution of the vertical electric field (that is, the zonal plasma drift), and the second term represents the contribution of the zonal wind in the F region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zonal winds from CHAMP provide no suitable explanation for that longitudinal variation. Park and Lühr [] showed that E region dynamics has a strong influence on the F region currents. We may well see the response of a tidal effect at E layer altitude.…”
Section: Discussionmentioning
confidence: 99%
“…The second term, −σ P E z , represents the current generated by the polarized electric field. Park and Lühr (2013) studied the relative contributions of these two components to the vertical current in the F region. They found that the current driven by the radial electric field is opposite to the wind dynamo current, whereas the vertical current of the F layer is mainly contributed by the wind dynamo.…”
Section: Effects Of Tides On Diurnal Irc Distributionmentioning
confidence: 99%